Assessing family function: older adults vs. care nurses: a cross-sectional comparative study - Mei-Wen Wang; Ya-Mei Chen (BMC, 2024)
Abstract Background This study aimed to assess family function in home care for older adults. Understanding family dynamics is essential for providing quality care to older adults choosing to age in place. Methods In a cross-sectional study, 53 patients aged 65 or older receiving home care were evaluated, along with four home care nurses. The General Function of Family Assessment Device (FAD-GF) was used for self-assessment to examine family resources. Results Only 5.7% of older adults reported good family function. Strong correlations were found between assessments by nurses and older adults. Among the six aspects of family function, "problem solving," "communication," "affective responsiveness," and the overall results showed no disparities between the evaluations of older adults and nurses. Conclusions Home care nurses can effectively assess family function using the FAD-GF, particularly after six months of care. This assessment can help identify family issues and enhance home care quality through nurse training in FAD-GF application.